Paradigms and Fallacies: Rethinking Northeast Asian Security and Its Implications for the Korean Peninsula - Park, Hun Joo (INTERNATIONAL JOURNAL OF KOREAN UNIFICATION STUDIES, 2007)
This article examines the changing characteristics of international politics in Northeast Asia; a politics which is fundamentally distrustful, conflict-ridden, and power and interest-centric and the implications of such changes for the region and the Korean peninsula especially in the post-Cold War era. There is no doubt that such a power and interest-centric realist paradigm has maintained a certain dominance as a means of explaining the lack of reconciliation or institutionalization of regional cooperation both in postwar and post-Cold War Northeast Asia. When it comes to accounting for the lack of institutionalized multilateralism or security cooperation, however, the otherwise robust analytic power of the realist perspective becomes somewhat “sterile.” This is so because realists assume that the values, preferences, and goals of the units or nation states as largely fixed or determined by the anarchical international system. Such a realist paradigm has frequently led to a self-fulfilling prophecy: as if inevitably pressured by the system―or by confusing the realist assumptions with the reality ― states often end up pursuing their narrow and myopic national interests, further exacerbating the security dilemmas and problems for all concerned. What is most strikingly pronounced is the continued primacy of such contending national interests in Northeast Asian affairs, as manifested in the North Korean nuclear deadlock and the close integration of Japanese foreign policy with America’s global anti-terror war. The present article scrutinizes, in particular, the uniquely increasing trend in military spending in post-Cold War Northeast Asia as a way of further documenting these ominous changes as well as the problematic consequences of what have been arguably erroneous policy paradigms underlying the state behaviors under examination here. To help prevent the current security dilemmas from spiraling into a slippery and perilous path towards an arms race requires that the states under consideration and their policymakers change their realist assumptions, redefine their self-interests, and learn to embrace international societal norms and perspectives which are rooted firmly within this reality.
Keywords: paradigms; Northeast Asian security; foreign policy; military spending; post-Cold War era; paradigms; Northeast Asian security; foreign policy; military spending; post-Cold War era